PENGARUH CITRA MEREK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN DAN KEPUASAN KONSUMEN DIMODERASI KEPERCAYAAN KONSUMEN PRODUK NU SKIN DI KOTA PEKANBARU - Rima Guspita; Zulkarnain; Samsir (Ikatan Sarjana Ekonomi Indonesia Cabang Pekanbaru, 2019)
Today's competition in the world of beauty and body care products requires every bank to survive well. Therefore, each company is required to be able to increase satisfaction and consumer purchasing decisions, because both of these are important factors in determining success in the face of competition. Based on these problems, this study aims to determine the Effect of Price Brand Image, and Promotion of Purchasing Decisions and Consumer Satisfaction Moderated Consumer Trust in Nu Skin Products in Pekanbaru City. This research was conducted on Nu Skin Product Consumers in Pekanbaru City, the number of samples used was 260 people. Data collection techniques using questionnaires, and data analysis using SEM with WarPls version 3.0. The results of the study show that: 1) There is an effect of brand image, price, and promotion influence on purchasing decisions. 2) There is an influence of brand image, price, and promotion influence on purchasing decisions moderated by consumer confidence. 3) There is the influence of purchasing decisions on customer satisfaction. Based on the results of the research, Nu Skin in Pekanbaru City must be able to overcome the problem of brand image, price and promotion, in order to increase purchasing decisions and customer satisfaction, and improve consumer confidence, so that purchasing decisions can be improved.